PENGARUH PELAYANAN PERPUSTAKAAN TERHADAP KEPUASAN PEMUSTAKA DI PERPUSTAKAAN FAKULTAS ADAB DAN HUMANIORA UIN RADEN FATAH PALEMBANG - Kris Setyaningsih (El-Idare, 2016)
The study evaluated the effect of library services to the satisfaction of library visitors in culture and humanities faculty uin Raden Fatah Palembang, motivated by the limitations of the materials needed by pemustaka. This type of research is a kind of quantitative research. Data analysis used the "t". Data obtained through observations, questionnaires and documentation originating from pemustaka numbered 40 students of faculty of Adab and Humanities. Results of the analysis showed no significant relationship between library services to the satisfaction pemustaka after being renovated in culture and humanities faculty library UIN Raden Fatah Palembang. This is evident from the results of the study showed that to = 2.89 is greater than the "t" good table at significant level of 5% (2.02) as well as the significant level of 1% (2.71) that can be represented 2.02 < 2.89> 2.71. Therefore, the null hypothesis is rejected and the alternative hypothesis is accepted which means that there is a positive influence on the Service Satisfaction pemustaka library after being renovated at the Library of the Faculty of Adab and Humanities UIN Raden Fatah Palembang.